No Link Between Striatal Dopaminergic Axons and Dopamine Transporter Imagingin Parkinson’s Disease - Honkanen Emma A.; Saari Laura; Orte Katri; Gardberg Maria; Noponen Tommi; Joutsa Juho; Kaasinen Valtteri (Wiley-Blackwell Publishing Ltd., 2022)
Background:Brain dopamine transporter binding hasbeen considered a possible biomarker for nigrostriataldegeneration in PD.Objective:To investigate whether dopamine trans-porter binding is associated with the number of dopa-minergic neurites in the putamen.
Methods:Tyrosine hydroxylase–positive nervefiberswere counted from postmortem putamen sections takenfrom 14 parkinsonism patients who had been scannedwith dopamine transporter single-photon emission com-puted tomography antemortem. Fiber counts were cor-related with putamen dopamine transporter binding andSN neuron counts.
Results:The putamen dopamine transporter specificbinding ratio did not correlate with the putamen tyrosinehydroxylase–positive axon counts (r = 0.00;P= 1.0; PDpatients: r = 0.07;P= 0.86). The nigra neuron counts had a positive correlation with the putamen tyrosinehydroxylase–positive axon counts.
Conclusions:Striatal dopamine transporter imagingdoes not associate with axonal nor somal loss of thenigrostriatal neurons in PD. It may reflect dopaminergicactivity rather than number of surviving neurons or theirstriatal projection axons.